Prevalence and factors associated with outcome of labour induction: Prospective longitudinal study at a tertiary hospital in Kampala, Uganda - Kombe, Dismus Ramadhan; Zaake, Daniel; Byaruhanga, Romano (Ethiopian Journal of Reproductive Health, 2026)
Objective: To study the prevalence, outcome and factors associated with successful induction of labour Design: prospective longitudinal study Setting: A tertiary non for profit teaching hospital in Kampala, Uganda Participants: 300 pregnant women who were induced of labour at the hospital during the study period of January to August 2023. Primary and secondary outcome measures: The prevalence of induction of labour, outcome of labour induction as successful or failed induction and the secondary outcomes including mode of delivery, maternal/neonatal complications and factors associated with successful induction of labour. Results: The prevalence of labour induction was 16.5%. Successful induction of labour occurred in 63% while 21% had failed induction. Having a favourable Modified Bishop’s score (6-13) at start of induction was associated with 100% success. The following non cervical factors were positively associated with successful induction of labour: Normal BMI (aOR=3.98, CI=1.148-13.825,P=0.029), parity?1 (aOR=7.725,CI=2.130-28.017,P=0.002), prolonged latent labour as an indication (aOR=7.691,CI=2.118-27.983,P=0.002), postdates/post-term as an indication for induction (aOR=3.045,CI=1.339-6.921,P=0.008), emergency induction (aOR=2.714,CI=1.365 5.395, P=0.004) and attending at least 4 antenatal care visits (aOR=2.638,CI=1.018-6.836,P=0.046). Starting the induction of labour with intact amniotic membranes was however, negatively associated with successful labour induction (aOR=0.124, CI=0.016-0.954, P=0.045). Conclusion: The prevalence of labour induction at our facility is higher than the average for LMICs but still lower than global prevalence. Induction of labour should be encouraged in presence of appropriate indication as the success rates are comparable to those in other LMICs and the globe.